Potencial de proliferación de las células madre de la papila apical en una biotinta a base de celulosa nanofibrilar (2022)
Objective: Evaluate the proliferation potential of aplical papilla stem cells in a nanofibrillar cellulose bioink. Materials and methods: In vitro study. The stem cells were obtained from a patient’s apical papilla, who provided express consent. The cell culture was completed up to fourth passage, they were mixed with nanofribillar cellulose from CELLINK Skin commercial enterprise and 4 groups with 3 1x1 constructs in a CELLINK Bio X Bioprinter. The days 1, 7 and 14 have been defined. Cellular characterization, Hematoxylin & eosin, PCNA and DAPI qualitative tests were conducted. Viability and cellular proliferation test were completed through Live-Dead and WSTI.